Abatement effects of different soil amendments on continuous cropping of Codonopsis pilosula - Yang, Zhaodi; Qiu, Daiyu; Jiang, Kan; Du, Maoxiao; Li, Hongyan (Frontiers in Plant Science, 2024)
Introduction Codonopsis pilosula is widely sought-after in China as a substitute for the more expensive ginseng. Continuous cropping of C. pilosula supports a vibrant health-supplement industry but requires significant inputs of fertilizers which increase production costs and degrade the environment. Methods Here, three environmentally-friendly natural fertilizers, including biochar, bacterial fertilizer, and vermicompost, were used at different concentrations (undiluted, diluted 10 times, diluted 50 times) to determine their efficacy in seed germination and growth physiology of C. pilosula in continuous cropping. Results The results showed that biochar, bacterial fertilizer, and vermicompost with different concentrations of leachate could all increase the germination rate, germination potential and germination index of C. pilosula seeds treated with inter-root soil leachate of continuous C. pilosula; increase the activity of antioxidant enzymes (superoxide dismutase and peroxidase) in C. pilosula seedlings under the stress of inter-root soil leachate of continuous C. pilosula, reduce the over-accumulation of malondialdehyde (MDA) content, and increase the resistance of C. pilosula seedlings. After transplanting, superoxide dismutase (SOD) activity increased by an average of 16.1%. Peroxidase (POD) levels showed an average increase of 16.4%. Additionally, there was a significant reduction in the MDA content, with an average decrease of 50%, and the content of osmotic-regulating substances (free proline content and soluble protein content) exhibited a significant increase. Discussion In conclusion, biochar, bacterial manure, and vermicompost have the potential to overcome the challenges of extensive fertilizer use in continuous cropping of C. pilosula.